2017
DOI: 10.1259/bjr.20160803
|View full text |Cite
|
Sign up to set email alerts
|

Is the necrosis/wall ADC ratio useful for the differentiation of benign and malignant breast lesions?

Abstract: The necrosis/wall ADC ratio appears to be a reliable and promising tool for discriminating breast carcinomas from abscesses using DWI. Advances in knowledge: ADC values of the necrosis obtained by DWI are valuable for malignant-benign differentiation in necrotic breast lesions. The necrosis/wall ADC ratio appears to be a reliable and promising tool in the breast imaging field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Necrosis/wall ADC ratio (NWADCr) is the ratio of the ADC values of the necrosis to the wall. It was shown that NWADCr is statistically different for benign and malignant necrotic breast lesions [1]. Wall of carcinoma and necrosis of an abscess will demonstrate more diffusion restriction because of first one having high cellularity, the large size of nucleus, intracellular macromolecules, the limited size of the extracellular matrix, and the second one showing high viscosity and cellular debris.…”
Section: What Are the Clinical Applications?mentioning
confidence: 99%
See 1 more Smart Citation
“…Necrosis/wall ADC ratio (NWADCr) is the ratio of the ADC values of the necrosis to the wall. It was shown that NWADCr is statistically different for benign and malignant necrotic breast lesions [1]. Wall of carcinoma and necrosis of an abscess will demonstrate more diffusion restriction because of first one having high cellularity, the large size of nucleus, intracellular macromolecules, the limited size of the extracellular matrix, and the second one showing high viscosity and cellular debris.…”
Section: What Are the Clinical Applications?mentioning
confidence: 99%
“…Diffusion-weighted magnetic resonance imaging (DW- MRI) is a non-contrast procedure, measuring the motion of water particles in vivo and analyzing microscopic tissue structure: cellularity, membrane integrity, viscosity, fibers, tubules, organelles, and macromolecules [1]. During the acquisition, motion-sensitizing gradients are used.…”
Section: Introductionmentioning
confidence: 99%
“… 13 The necrosis/wall ADC ratio would be more efficient for malignant-benign differentiation in necrotic breast lesions than for measuring only ADC of the wall. 28 Our article presented that the mean inside/wall ADC ratio (1.20 ± 0.28) of the lung cancers was remarkably higher than that (0.74 ± 0.14) of the pulmonary abscesses ( P < .0001). Furthermore, the mean inside ADC value (1.33 ± 0.32 × 10 −3 mm 2 /s) of the lung cancers was remarkably higher than that (0.94 ± 0.42 × 10 −3 mm 2 /s) of the pulmonary abscesses ( P = .0019).…”
Section: Discussionmentioning
confidence: 63%
“…Currently, breast MRI has been reported to be highly accurate in defining the subgross morphological prognostics (9,14,23,25) such as tumor dimensions and spread as well as lesion characterization (26,27). Also, multifocality and extensive disease are the negative prognostic factors, independent of tumor size (18,28).…”
Section: Discussionmentioning
confidence: 99%